Direct route from ethanol to pure hydrogen through autothermal reforming in a membrane reactor: Experimental demonstration, reactor modelling and design. (15th January 2018) - Spallina, V.; Matturro, G.; Ruocco, C.; Meloni, E.; Palma, V.; Fernandez, E.; Melendez, J.; Pacheco Tanaka, A.D.; Viviente Sole, J.L.; van Sint Annaland, M.; Gallucci, F.
Abstract: This work reports the integration of thin (∼3–4 μm thick) Pd-based membranes for H2 separation in a fluidized bed catalytic reactor for ethanol auto-thermal reforming. The performance of a fluidized bed membrane reactor has been investigated from an experimental and numerical point of view. The demonstration of the technology has been carried out over 50 h under reactive conditions using 5 thin Pd-based alumina-supported membranes and a 3 wt%Pt-10 wt%Ni catalyst deposited on a mixed CeO2 /SiO2 support. The results have confirmed the feasibility of the concept, in particular the capacity to reach a hydrogen recovery factor up to 70%, while the operation at different fluidization regimes, oxygen-to-ethanol and steam-to-ethanol ratios, feed pressures and reactor temperatures have been studied. The most critical part of the system is the sealing of the membranes, where most of the gas leakage was detected. A fluidized bed membrane reactor model for ethanol reforming has been developed and validated with the obtained experimental results. The model has been subsequently used to design a small reactor unit for domestic use, showing that 0.45 m 2 membrane area is needed to produce the amount of H2 required for a 5 kWe PEM fuel-cell based micro-CHP system. Highlights: Ethanol membrane reactor demonstrated for more than 50 h operation. 100% ethanol conversion achieved using Pt/Ni-based catalyst. Overall HRF of 67% achieved in auto-thermal operation. Validation of a membrane fluidized bed reactor model successfully achieved.